Radical‐Enabled Bicyclization Cascades of Oxygen‐Tethered 1, 7‐Enynes Leading to Skeletally Diverse Polycyclic Chromen‐2‐ones. Issue 3 (16th February 2017) - Jiang, Bo; Li, Jie; Pan, Yuanyuan; Hao, Wenjuan; Li, Guigen; Tu, Shujiang
Abstract : Catalytic bicyclization cascades of oxygen‐tethered 1, 7‐enynes with simple cycloalkanes or aryl sulfonhydrazides have been established via subsequent multiple C‐C bond‐forming events from alkynyl/alkenyl functions, delivering a series of densely functionalized tetracyclic chromen‐2‐ones in a functional‐group‐compatible manner. In the former, Fe‐catalyzed spiro‐bicyclization involves radical addition, 6‐exo‐dig cyclization, H‐abstraction and 5‐endo‐trig cyclization sequences under mild conditions, resulting in new spiro‐fused cyclopenta[ c ]chromen‐2‐ones via dual α, α ‐C(sp 3 )‐H abstractions. The latter enables in‐situ sulfonylation and desulfonylation of oxygen‐tethered 1, 7‐enynes to realize the construction of multiple C‐C bonds, thereby leading to the formation of naphtho[2, 3‐ c ]chromen‐6‐ones. Abstract :